Missionary ecclesiology in the early Pentecostal years - M. Mokienko (Українське Pелігієзнавство, 2013)
The most dynamic segment of the Protestant enclave of the twentieth century. consider the Pentecostal movement. His limits and variability have greatly corrected the global religious atlas. By some estimates, the number of followers of various Pentecostal communities reached the limit of millenia from 400 to 600 million followers75. Despite the doubts that may arise in the predictions of D. Barrett and others, it is difficult to deny that the success of Pentecostal / charismatic missionary activity in the second half of the twentieth century was spectacular.